Using «stonebreaker» (Phyllantus niruri) as therapy for struvite urolithiasis in a pet rabbit (Oryctolagus cuniculus) - Quevedo U., Miryam (2015)
Urolithiasis is a common disease in companion animals, but the etiopathogenesis and frequency in rabbits is poorly known. Conventional therapy can be surgical or medical. An alternative treatment based on the use of the plant «stonebreaker» (Phyllantus niruri) is commonly used in human urolithiasis in Peruvian traditional medicine, despite pharmacologic mechanisms are not completely understood yet. It is reported the case of a male rabbit showing dysuria and abdominal pain. Radiologic examination revealed the presence of a radiopaque body in the urethra. Urolithiasis was diagnosed, surgery was scheduled for the next morning and «stonebreaker» tea was suggested as a complementary therapy. The following day the owner found the urolith near the pet’s hutch. Ultrasonography revealed the absence of calculus in the urinary tract. Laboratory analysis revealed the urolith was composed by ammonium magnesium phosphate.